Integration of Technology in Learning Activities: E-Module on Islamic Religious Education Learning for Vocational High School Students - Fahmi, Ahmad Nur; Yusuf, Munawir; Muchtarom, Mohammad (Universitas Pendidikan Ganesha, 2021)
Technological advancement encourage a change in learning paradigm towards digital-based learning and a shift in the role of the teacher to become a learning facilitator, not the only source of learning. Innovation in the use of e-modules was a reflection of the integration of ICT into the learning process. This study aimed to develop an electronic module that was suitable for use in learning Islamic religious education for vocational high school students. This research is classified as Research and Development (R&D) research with ADDIE procedures consisting of Analysis, Design, Development, Implementation and Evaluation. However, this research was limited to the development stage. The sample of this study consisted of one material expert, two media experts and three teachers of Islamic religious education subjects. The data analysis technique uses a descriptive analysis techniques with percentages to describe the feasibility value of the electronic module (e-modul). Based on the results of the study, the results of the assessment of the e-module places by each assessor with details, namely the material expert assessment obtained 96.1%, the media expert assessment 95.1% and the assessment conducted by the subject teacher received a score of 96.1%. 83, 3%, therefore the e-module product developed is suitable for being used as a learning activities. The results of this study can certainly be used as a basis for educators in order to implement electronic digital format module technology into learning activities.